Solutions to linear matrix ordinary differential equations via minimal, regular, and excessive space extension based universalization - Sevda, Üsküplü Altınbaşak; Metin, Demiralp (Springer Science and Business Media LLC, 2010)
zbMATH Open Web Interface contents unavailable due to conflicting licenses.
Keywords: numerical examples; convergence; Linear ordinary differential equations and systems; Analytical theory of ordinary differential equations: series, transformations, transforms, operational calculus, etc.; Numerical methods for initial value problems involving ordinary differential equations; majorant series; error estimates; ordinary differential equations; space extension; Stability and convergence of numerical methods for ordinary differential equations; linear matrix ordinary differential equations; perturbation solutions; Error bounds for numerical methods for ordinary differential equations